Unravelling the origins of anomalous diffusion: From molecules to migrating storks - Ohad Vilk; Erez Aghion; Tal Avgar; Carsten Beta; Oliver Nagel; Adal Sabri; Raphael Sarfati; Daniel K. Schwartz; Matthias Weiss; Diego Krapf; Ran Nathan; Ralf Metzler; et al. (Physical Review Research, 2022)
Anomalous diffusion or, more generally, anomalous transport, with nonlinear dependence of the mean-squared displacement on the measurement time, is ubiquitous in nature. It has been observed in processes ranging from microscopic movement of molecules to macroscopic, large-scale paths of migrating birds. Using data from multiple empirical systems, spanning 12 orders of magnitude in length and 8 orders of magnitude in time, we employ a method to detect the individual underlying origins of anomalous diffusion and transport in the data. This method decomposes anomalous transport into three primary effects: long-range correlations (“Joseph effect”), fat-tailed probability density of increments (“Noah effect”), and nonstationarity (“Moses effect”). We show that such a decomposition of real-life data allows us to infer nontrivial behavioral predictions and to resolve open questions in the fields of single-particle tracking in living cells and movement ecology.